Antioxidant-rich beetroot juice does not adversely affect acute neuromuscular adaptation following eccentric exercise. Issue 8 (18th April 2017) - Clifford, Tom; Bell, Oliver; West, Daniel J.; Howatson, Glyn; Stevenson, Emma J.
ABSTRACT: This study examined the effects of beetroot juice on the repeated bout effect (RBE) to eccentric exercise. Twenty-nine recreationally active males performed two bouts of 100-drop jumps, separated by 14–21 days. Using a double-blind, independent groups design, participants consumed either a higher dose beetroot juice (H-BT; 250 ml, n = 10), a lower dose beetroot juice (L-BT; 125 ml, n = 9) or an isocaloric placebo (PLA; 250 ml, n = 10) for 3 days after bout 1; no drinks were consumed after bout 2. Maximal isometric voluntary contraction (MIVC), countermovement jump (CMJ), pressure-pain threshold (PPT) and creatine kinase (CK) were measured pre, post, 24, 48 and 72 h following both bouts. In bout 2, CMJ and MIVC recovered quicker and CK activity was attenuated (versus bout 1) ( P < 0.05) in all groups, demonstrating an RBE. At 24 h post bout 1, MIVC was 84.1 ± 16.1, 83.6 ± 11.6, 79.7 ± 15.1% relative to baseline values in the H-BT, L-BT and PLA groups, respectively; at 24 h post bout 2, MIVC recovered to 90.7 ± 13.7, 92.9 ± 6.9, 87.8 ± 6.9, in the H-BT, L-BT and PLA groups, respectively. These findings suggest that supplementation with antioxidant-rich beetroot juice does not adversely affect acute adaptations to a bout of eccentric exercise.